Rozwiązane

Oblicz.
d) ([tex]\sqrt{x} 2 - 4)^3 = ?[/tex]
e) (1 + 2[tex]\sqrt{x} 5)^3 = ?[/tex]
f) (2[tex]\sqrt{x}3 - 3)^3 = ?[/tex]
g) ([tex]\sqrt{x} 2 + \sqrt{x} 3)^3 = ?[/tex]
h) ([tex]\sqrt{x} 3 - \sqrt{x}6)^3 = ?[/tex]



Odpowiedź :

Odpowiedź i szczegółowe wyjaśnienie:

Korzystamy ze wzorów:

[tex](a-b)^{3}=a^{3}-3a^{2}b+3ab^{2}-b^{3}\\\\(a+b)^{3}=a^{3}+3a^{2}b+3ab^{2}+b^{3}[/tex]

[tex]d)\ \\(\sqrt2-4)^2=(\sqrt2)^3-3\cdot(\sqrt2)^2\cdot4+3\cdot\sqrt2\cdot4^2-4^3=\\\\=2\sqrt2-3\cdot2\cdot4+3\cdot\sqrt2\cdot16-64=2\sqrt2-24+48\sqrt2-64=\\\\=50\sqrt2-88[/tex]

[tex]e)\ \\(1+2\sqrt5)^3=1^3+3\cdot1^2\cdot2\sqrt5+3\cdot1\cdot(2\sqrt5)^2+(2\sqrt5)^3=\\\\=1+6\sqrt5+3\cdot4\cdot5+8\cdot5\sqrt5=1+6\sqrt5+60+40\sqrt5=\\\\=61+46\sqrt5[/tex]

[tex]f)\ \\(2\sqrt3-3)^3=(2\sqrt3)^3-3\cdot(2\sqrt3)^2\cdot3+3\cdot2\sqrt3\cdot3^2-3^3=\\\\=8\cdot3\sqrt3-3\cdot4\cdot3\cdot3+6\sqrt3\cdot9-27=\\\\=24\sqrt3-108+54\sqrt3-27=\\\\=78\sqrt3-135[/tex]

[tex]g)\ \\(\sqrt2+\sqrt3)^3=(\sqrt2)^3+3\cdot(\sqrt2)^2\cdot\sqrt3+3\cdot\sqrt2\cdot(\sqrt3)^2+(\sqrt3)^3=\\\\=2\sqrt2+3\cdot2\cdot\sqrt3+3\sqrt2\cdot3+3\sqrt3=\\\\=2\sqrt2+6\sqrt3+9\sqrt2+3\sqrt3=11\sqrt2+9\sqrt3[/tex]

[tex]h)\\(\sqrt3-\sqrt6)^3=(\sqrt3)^3-3\cdot(\sqrt3)^2\cdot\sqrt6+3\sqrt3\cdot(\sqrt6)^2-(\sqrt6)^3=\\\\=3\sqrt3-3\cdot3\sqrt6+3\sqrt3\cdot6-6\sqrt6=\\\\=3\sqrt3-9\sqrt6+18\sqrt3-6\sqrt6=21\sqrt3-15\sqrt6[/tex]